A Model of the Potassium-Oxygen Battery and its Application in Cathode Design. Issue 6 (1st June 2022) - Küpper, Jannis; Li, Xianglin; Simon, Ulrich
Abstract : The potassium-oxygen battery (KOB) is a new type of metal-oxygen battery with high rechargeability and long cycle life. Currently, the energy density is rather limited and must be improved for KOB to become a viable energy storage technology for practical applications. In this study, a two-dimensional, multiphase KOB model is developed to design an optimized cathode structure. The model is validated and is used to study the influence of cathode porosity, surface area, and thickness on the discharge behavior. Higher cathode porosity and surface area are found to increase the discharge capacity and lower the discharge overpotential. However, using a microporous cathode may not be ideal for KOB. The electronic transport properties of the discharge product KO2 are assessed, suggesting an effectively higher conductivity of KO2 than previously predicted. In consequence, the formation of large KO2 deposits with several μ m thickness may effectively inhibit oxygen transport in microporous materials. Thus, a hierarchical cathode porosity together with an optimized current collector design may be the key to significantly higher discharge performance.